The role of compensation as a moderating variable in peaffect workload teon employee performance - I Made Kartika; Kadek Mega Dwiyanti; Putu Gede Denny Herlambang; I Made Adi Suwandana (Jurnal Mantik, 2023)
The success of an organization cannot be separated from the management of reliable and professional human resources (HR), so that the organization can achieve success in achieving the goals that have been set. HR management must be directed at efforts that are able to explore the potential of human resources in order to make a positive contribution to the organization in the form of optimal individual and team performance. Good performance will certainly increase the value of the company through the level of service and the quality of goods or services offered by the company. The purpose of this study was to analyze the effect of workload on employee performance at PT GIEB Indonesia, and to analyze the moderating effect of compensation on the effect of workload on employee performance at PT GIEB Indonesia. The research design is quantitative with correlational research type. Sampling using saturated sampling, namely all employees of PT. GIEB Indonesia Denpasar as many as 39 people. The data collection technique was carried out by distributing questionnaires to respondents. Data analysis techniques using SEM-PLS with the help of Smart PLS software. Research conclusions include: 1) Workload has a positive and significant effect on employee performance at PT GIEB Indonesia. This shows that the higher the employee's workload, it will motivate employees to work better so that they can show better performance; and 2) Compensation is not able to moderate the influence of workload on employee performance. Compensation is not able to moderate the effect of workload on employee performance.